Plant Organellar Proteomics in Response to Dehydration: Turning Protein Repertoire into Insights - Gupta, Deepti B.; Rai, Yogita; Gayali, Saurabh; Chakraborty, Subhra; Chakraborty, Niranjan (Frontiers in Plant Science, 2016)
Stress adaptation or tolerance in plants is a complex phenomenon involving changes in physiological and metabolic processes. Plants must develop elaborate networks of defense mechanisms, and adapt to and survive for sustainable agriculture. Water-deficit or dehydration is the most critical environmental factor that plants are exposed to during their life cycle, which influences geographical distribution and productivity of many crop species. The cellular responses to dehydration are orchestrated by a series of multidirectional relays of biochemical events at organelle level. The new challenge is to dissect the underlying mechanisms controlling the perception of stress signals and their transmission to cellular machinery for activation of adaptive responses. The completeness of current descriptions of spatial distribution of proteins, the relevance of subcellular locations in diverse functional processes, and the changes of protein abundance in response to dehydration hold the key to understanding how plants cope with such stress conditions. During past decades, organellar proteomics has proved to be useful not only for deciphering reprograming of plant responses to dehydration, but also to dissect stress–responsive pathways. This review summarizes a range of organellar proteomics investigations under dehydration to gain a holistic view of plant responses to water-deficit conditions, which may facilitate future efforts to develop genetically engineered crops for better adaptation.